Seroprevalence of Ehrlichia canis, Ehrlichia chaffeensis and Ehrlichia ewingii in dogs in North America - Beall, Melissa J.; Alleman, A. Rick; Breitschwerdt, Ed B.; Cohn, Leah A.; Couto, C. Guillermo; Dryden, Michael W.; Guptill, Lynn C.; Iazbik, Cristina; Kania, Stephen A.; Lathan, Patty; Little, Susan E.; Roy, Alma; et al. (My University, 2012)
Background: This study evaluated the exposure of dogs to three different Ehrlichia spp. in the south and central regions of the United States where vector-borne disease prevalence has been previously difficult to ascertain, particularly beyond the metropolitan areas. Methods: Dog blood samples (n = 8,662) were submitted from 14 veterinary colleges, 6 private veterinary practices and 4 diagnostic laboratories across this region. Samples were tested for E. canis, E. chaffeensis and E. ewingii specific antibodies using peptide microtiter ELISAs. Results: Overall, E. canis, E. chaffeensis and E. ewingii seroprevalence was 0.8%, 2.8%, and 5.1%, respectively. The highest E. canis seroprevalence (2.3%) was found in a region encompassing Arkansas, Louisiana, Oklahoma, Tennessee and Texas. E. chaffeensis seroreactivity was 6.6% in the central region (Arkansas, Kansas, Missouri, and Oklahoma) and 4.6% in the southeast region (Georgia, Maryland, North Carolina, South Carolina, Tennessee and Virginia). Seroreactivity to E. ewingii was also highest in the central region (14.6%) followed by the southeast region (5.9%). The geospatial pattern derived from E. chaffeensis and E. ewingii seropositive samples was similar to previous reports based on E. chaffeensis seroreactivity in white-tailed deer and the distribution of human monocytic ehrlichiosis (HME) cases reported by the CDC. Conclusions: The results of this study provide the first large scale regional documentation of exposure to E. canis, E. chaffeensis and E. ewingii in pet dogs, highlighting regional differences in seroprevalence and providing the basis for heightened awareness of these emerging vector-borne pathogens by veterinarians and public health agencies.
Keywords: Ehrlichia; E. canis; E. chaffeensis; E. ewingii; Dog; Tick; Prevalence